RNA-Seq Reveals miRNA and mRNA Co-regulate Muscle Differentiation in Fetal Leizhou Goats - Ye, Junning; Zhao, Xiuhui; Xue, Huiwen; Zou, Xian; Liu, Guangbin; Deng, Ming; Sun, Baoli; Guo, Yongqing; Liu, Dewu; Li, Yaokun (Frontiers in Veterinary Science, 2022)
Muscle differentiation is an essential link in animal growth and development, and microRNA and mRNA are indispensable in skeletal muscle differentiation. In order to increase the meat quality and meat production of the Leizhou goat, it is necessary to understand the molecular mechanism of its skeletal muscle differentiation. By RNA sequencing (RNA-SEQ), we established miRNA-mRNA profiles of Leizhou goats at three stages: fetal day 70, 90, and 120. There were 991 differently expressed mRNAs and 39 differentially expressed miRNAs found, with the differentially expressed mRNAs mainly enriched in calcium ion binding, ECM-receptor interaction, and Focal adhesion. CKM and MYH3, two muscle differentiation markers, were significantly differentially expressed during this period. In addition, we found that chi-miR-129-5p, chi-miR-433, and chi-miR-24-3p co-regulate muscle differentiation with their target genes. Finally, we can confirm that muscle differentiation occurred in Leizhou goat between 90 and 120 days of the fetus. This study is helpful to better explore the molecular mechanism of goat muscle differentiation.